Eksistensi Seni Pertunjukan Wayang di Tengah Masyarakat Pekalongan : Antara Tradisi dan Modernitas - Daffa Afrizal Maulana; Dafa Hermafahriza; Dwijo Ferdianto; Jamaluddin Husein; Dimas Setiaji Prabowo (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
Wayang is an intangible cultural heritage of Indonesia recognized by UNESCO since 2003 and serves as a medium for entertainment, education, and the transmission of cultural values. Technological developments and changes in people's entertainment consumption patterns present both challenges and opportunities for the sustainability of wayang performing arts. This study aims to describe efforts to preserve traditional values ​​and forms of adaptation of wayang performing arts to modernity in Doro District, Pekalongan Regency. The study uses a qualitative approach with descriptive methods. Data were obtained through observation, in-depth interviews with puppeteers and founders of wayang studios, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the existence of wayang performing arts is maintained through intergenerational inheritance carried out sustainably through art studios, youth development, and organizing performances at various traditional activities and community celebrations. In addition, artists carry out various forms of adaptation by utilizing social media as a means of promotion, organizing live broadcasts of performances, inviting guest stars, and developing more creative performance concepts without eliminating the main values ​​of wayang. Local government support through organizing festivals, facilitating performances, and community development also strengthens preservation efforts. This research shows that the sustainability of wayang performance art depends on a balance between preserving tradition and adapting to technological developments, changing audience characteristics, and socio-cultural dynamics.